Rapid Voltammetric Screening Method for the Assessment of Bioflavonoid Content Using the Disposable Bare Pencil Graphite Electrode - Iulia Gabriela David (MDPI AG, 2021)
Hesperidin (HESP) is a plant bioflavonoid found in various nutritional and medicinal products. Many of its multiple health benefits rely on the compound’s antioxidant ability, which is due to the presence of oxidizable hydroxyl groups in its structure. Therefore, the present study aimed to investigate the electrochemical behavior of HESP at a cheap, disposable pencil graphite electrode (PGE) in order to develop rapid and simple voltammetric methods for its quantification. Cyclic voltammetric investigations emphasized a complex electrochemical behavior of HESP. The influence of the electrode material, solution stability, supporting electrolyte pH, and nature were examined. HESP main irreversible, diffusion-controlled oxidation signal obtained at H type PGE in Britton Robinson buffer pH 1.81 was exploited for the development of a differential pulse voltammetry (DPV) quantitative analysis method. The quasi-reversible, adsorption-controlled reduction peak was used for HESP quantification by differential pulse adsorptive stripping voltammetry (DPAdSV). The linear ranges of DPV and DPAdSV were 1.00 × 10−7–1.20 × 10−5 and 5.00 × 10−8–1.00 × 10−6 mol/L with detection limits of 8.58 × 10−8 and 1.90 × 10−8 mol/L HESP, respectively. The DPV method was applied for the assessment of dietary supplements bioflavonoid content, expressed as mg HESP.